Pengetahuan Lokal Masyarakat Pulau Binongko dalam Sistim Ketahanan Pangan - Hidrawati, Hidrawati; Rianse, Usman; Iswandi, R. Marsuki; Arafah, Nur; Hamzah, Awaluddin (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
The research main reason is the Binongko Island community have indication vulnerable of food shortages due to limited of land resources, water and access to the surrounding area. In fact, Binongko society had not experienced problems with food stocks, because they have local knowledge in the food security system. This purpose research revealing and describing the local knowledge of Binongko society in the food security system. The study was conducted in December 2016-March 2017 at Binongko Island, Wakatobi Regency, Southeast Sulawesi Province. This qualitative research uses literature study techniques, orientation, observation and interviews with the snowball method. The results showed that Binongko Island community has local knowledge about the food security system in the form of (1) Development of mixed cropping patterns in more than one farming location with different planting and harvesting times. This is through a series of farming system local knowledge that starts with ritual bhelai, phitado, honowu/katambhari, bhija-bhija/bhatata, pajere'a, phidawu-phidongka and tompe’a; (2) Processing, preservation and foodstuffs storage are accordance with the type of foodstuffs and harvest time. Kalla'a and gadha are one of the storage containers as well as the preservation of the food; (3) Household food consumption patterns adhere to the values of shipping logistical arrangements system and internalization of the mother role as Pande Mantoroka in managing household food menus